The Influence of Agricultural, Manufacturing, and Mining Sector Output on Aceh's GRDP Growth: An Empirical Study Using Panel Data - Akhyarul Mulki; Uliya Azra; Ibnu Hajar (PT. Maju Malaqbi Makkarana, 2026)
The economic structure of Aceh Province is still dominated by the agriculture, forestry, and fisheries sectors, while the contribution of the manufacturing industry sector is relatively lagging. This condition indicates that the structural transformation process in Aceh has not yet taken place optimally, so that the economic growth that occurs tends to be quantitative, marked by an increase in aggregate output, but does not fully reflect an increase in the quality of the economic structure. This study aims to analyze the influence of the agriculture, manufacturing industry, and mining sectors on the growth of the Regional Gross Regional Domestic Product (GRDP) of Aceh Province. The approach used is quantitative with secondary data sources from the BPS of Aceh Province. This study uses panel data which is a combination of cross-regional data and time series data from 2019 to 2023. The results of the study indicate, first; the agricultural sector has a positive effect on GRDP. This is based on the probability value of the agricultural sector variable, which is 0.002. This value is smaller than 0.05. Second; the industrial sector has no effect on GRDP. This is based on the probability value of the industrial sector variable, which is 0.610. This value is greater than 0.05. Third; the mining sector has a positive effect on GRDP. This is based on the probability value of the mining sector variable, which is 0.001. Fourth; The agricultural, industrial and mining sectors have a joint influence on the dependent variable, namely GRDP in Aceh Province